The Care Apples and Their Implications on the Lifestyles of Women Caregivers in Bogotá, Colombia - Álvarez Sánchez, Yolanda; Ruiz Gómez, Patricia Paola (Sociedad y Economía, 2025)
The purpose of this manuscript is to identify the implications of care apples on the lifestyles of women caregivers in Bogotá, Colombia. Since their implementation (2020-2024), the care apples have developed an infrastructure of social services and essential care at the district level, targeting women from all socioeconomic backgrounds. Therefore, this manuscript seeks to answer the following question: What have been the implications of care apples on the lifestyles of women caregivers in Bogotá, Colombia? To address this question, a qualitative approach was adopted, along with research techniques typical of this approach, particularly the structured interview. Among the main conclusions is the self-recognition, visibility, and integration of care work—traditionally performed by women—as a mechanism for reducing gender inequalities and poverty.